2004
DOI: 10.1590/s1519-69842004000200012
|View full text |Cite
|
Sign up to set email alerts
|

Ureotelism is inducible in the neotropical freshwater Hoplias malabaricus (Teleostei, Erythrinidae)

Abstract: Increased environmental pH decreases ammonia transport through the gills, impairing nitrogenous waste. The consequent toxicity is usually drastic to most fishes. A few species are able to synthesize urea as a way to detoxify plasma ammonia. We studied three teleosts of the family Erythrinidae living in distinct environments, and assumed the biochemical behaviors would be different in spite of their being closely related species. Adult fish collected in the wild were submitted to alkaline water and the urea exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…However, the high arginase activity observed in the tissues of these organisms could be an indication of ureotelism in alkaline water, as observed by other workers (Mommsen & Walsh, 1992;Wood, 1993;Wright, 1995;Moraes & Polez, 2003).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…However, the high arginase activity observed in the tissues of these organisms could be an indication of ureotelism in alkaline water, as observed by other workers (Mommsen & Walsh, 1992;Wood, 1993;Wright, 1995;Moraes & Polez, 2003).…”
Section: Discussionsupporting
confidence: 66%
“…Also Ozan et al (1999), working on Rainbow trout (Oncorhynchus mykiss), found that arginase level in the liver was highest followed by kidney, skin, gills, muscle and eyes. The high level of arginase in the liver of these Tilapia species has been found to be caused by increase in the environmental pH which decreases ammonia transport through the gills, and then impairing nitrogenous waste (Campbell & Anderson, 1991;Moraes & Polez, 2003). The consequent toxicity is usually drastic to most fishes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A set of ornithine-urea cycle enzymes has been reported for some teleost species. Moreover, specific environmental conditions such as those created by ammonia increase (Saha & Ratha, 1994;Saha et al, 1999;Moraes & Polez, 2004b), alkaline waters (Randall et al, 1989;Moraes & Polez, 2004a), and confinement and/or crowding (Walsh et al, 1990;Walsh & Milligan, 1995) augment the presence of these enzymes. The Neotropical facultative airbreather Synbranchus marmoratus (marble swamp eel) is able to survive up to three months embedded in mud (Bicudo & Johansen, 1979), carrying out the gas-exchange process in the buccopharyngeal epithelium and in the branchial chamber.…”
Section: Introductionmentioning
confidence: 99%